THE ROLE OF THE ENVIRONMENT, FINANCIAL PERFOMANCE, AND MEDIA EXPOSURE IN CARBON EMISSION DISCLOSURE - Cahyaningrum, Chelsie; Hadiwibowo, Imam; Azis, Mohammad Taufik (AKUNTANSI DEWANTARA, 2025)
The study aims to analyze the impact of environmental performance, financial performance, and media exposure on carbon emission disclosure. The population used is the energy and basic materials sector companies listed on the Indonesian Stock Exchange in 2021-2023, with a total sample used of as many as 28 companies. This study uses eviews 8 as a measure. The data sources used in this research are from financial reports and sustainability reports accessed from both the BEI and company websites as well as PROPER KLHK. The results of this study showed that environmental performance and financial performance had no influence on the disclosure of carbon emissions, while media exposure had an influence over carbon disclosures.